SUPERVISI AKADEMIK VERSUS KUALITAS PEMBELAJARAN - Ermi Sola (Universitas Islam Negeri Alauddin Makassar, 2019)
The effort of improving the quality of education is a real continuing action by stakeholders, educational institution, and educators. School as a formal place is a place to make “men” to be “human”. A meaningful learning asks teacher to maximize their competences (pedagogic, professional, behavior, and social) in learning process. The Government Regulation Number 19 about National Standard of Education Number 1 Verse 3 that every school does planning, assessing, and supervising of learning process in order to reach effective and efficient learning process. Supervision is one of a bunch of ways to create a meaningful learning through a well-planned and structured guidance by the principal. At the end, a qualified learning is mirrored from the professional teacher as it is in the Government Regulation Number 19 about National Standard of Education Number 19 Verse 1 about “Process” Standard says that learning process must be interactive, inspiration, fun, motivate students to actively participate and spaces to be creative. Those are related to the student’s talents and their physics and psychological development.